Pendidikan Kesehatan Dengan Ceramah Dan Leaflet Meningkatkan Pengetahuan Ibu Hamil Terhadap Tanda Bahaya Kehamilan Tahun 2019 - Kumalasari, Kumalasari (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Pregnancy is a series of physiological changes in the body of the mother according to the gestational age. If accompanied by complications, changes in pregnancy can be serious and must be taken seriously for. Therefore, pregnant women need to recognize danger signs in pregnancy. This study aims to determine the effect of health education lecturer and leaflet on the knowledge of pregnant women about the danger of pregnancy. This Methode Quasi Experiment study that was designed with the One Group Pretest-Posttest design The lecture and leaflet, of 40 responden pregnant women at Simalingkar Medan Health Center were used as research samples after fulfilling the inclusion criteria. The results showed that before the health education, the mean knowledge of respondents was 12.95 and thereafter became 16.35. This study also found a significant effect between health education and the knowledge of pregnant women about the danger signs of pregnancy in Simalingkar Medan Health Center in 2019 (p = 0,000